Ethicality in B2B service delivery: examining the impact of individual and organisational ethics on firm performance through ethical leadership and climate - Sreejesh, S. (Journal of business ethics, 2025)
The criticality of ethical practices in B2B service delivery is increasingly recognised for its substantial impact on firm performance. However, there remains a gap in understanding how ethicality at managerial and staff levels translates into tangible business outcomes in B2B contexts. This study aims to bridge this gap, focusing on the impact of ethicality on perceived service delivery performance and firm performance, mainly through ethical leadership and climate lenses. The research objectives include unravelling the dynamics between staff-level ethical perceptions and managerial-level ethical practices and their collective impact on service delivery and firm performance. Employing a multilevel data collection and analytical framework, the study collected data from 5500 employees and 110 managers, providing a comprehensive view of ethical influences across different organisational strata. This approach facilitated a nuanced examination of how ethical perceptions and behaviours permeate through the organisational hierarchy. Major findings reveal that individual-level ethical perceptions enhance service delivery through positive citizenship behaviour of the employees and reduced opportunism. A culture of shared ethical values, reinforced by robust ethical leadership and a supportive climate, significantly bolstered firm performance at the organisational level. These insights contribute significantly to B2B theory by elucidating the mechanisms through which ethicality at various levels influences firm outcomes. The study underscores the importance of fostering an ethical culture at the individual level and holistically across the organisation to enhance service delivery and achieve superior firm performance.